Understanding digital marketing : marketing strategies for engaging the digital generation - Ryan, Damian (KoganPage, 2017)
"Marketing expert Damian Ryan looks at the world of digital marketing: how it got started, how it got to where it is today and where the thought leaders in the industry believe it is headed in the future. This new edition demonstrates in a practical and comprehensive way how to harness the power of digital media and use it to achieve the utmost success in business. It has also been thoroughly revised with more information, fresh examples and case studies, and new chapters on native advertising, video marketing, and the Internet of Things.Ryan deals with key topics in detail, including: search marketing, social media, mobile marketing, affiliate marketing, e-mail marketing, customer engagement and digital marketing strategies. He will help readers to: - choose online marketing channels to get their products and services to market - understand the origins of digital marketing and the trends that are shaping its future - achieve a competitive edge"--